Management of endotracheal tube air leak—a simple yet an effective manoeuver - Ghaffar, Waleed Bin; Tamraiz, Muhammad Adnan; Sohaib, Muhammad (Journal of the Pakistan Medical Association, 2023)
The management and maintenance of an airway can prevent life threatening complications. The handling of airway, especially in difficult airway and trauma patients, requires extreme caution. We have demonstrated a simple technique in the management of emergency airway, who was getting hypoxic due to severed endotracheal tube (ETT) cuff inflation line. A 20 G intravenous cannula was used, the leak was stopped, and the ETT balloon was inflated. Hence, the leakage and eventually hypoxia settled. We were able to manage emergency airway with this peculiar technique. The use of 20 G intravenous cannula can help to inflate a damaged ETT cuff inflation line. This is an inexpensive and effective manoeuver. Keywords: Airway management; Intubation; Intratracheal; Cervical Vertebrae.